A modified screening protocol for ARDS in patients with respiratory support based on SpO2 and FiO2: A single-center prospective, observational study - Yan Xia; Qiancheng Xu; Zhiyuan Guo; Huijuan Zhang; Yingya Cao; Yupeng Qi; Qun Chen; Weihua Lu (Journal of Intensive Medicine)
Background: The purpose is to formulate a modified screening protocol for acute respiratory distress syndrome (ARDS) in patients with respiratory support based on saturation of pulse oximetry (SpO2) and inspired oxygen concentration (FiO2). Methods: This prospective observational study was conducted from August to October 2020 at the Department of Critical Care Medicine of Yijishan Hospital Affiliated with Wannan Medical College. All patients admitted during the study period and required arterial blood gas analysis and electrocardiogram monitoring were included in this study. Patients with contraindications to arterial puncture, methemoglobinemia, carbon monoxide poisoning, and other factors that could affect data collection were excluded. The demographic and clinical data, immediate percutaneous SpO2, FiO2, arterial oxygen partial pressure (PaO2), and respiratory rate were recorded; and the SpO2/FiO2 ratio (SFR) and PaO2/FiO2 ratio (PFR) values were calculated according to the above information. The patients were divided into two cohorts by random number table: the establishment cohort and the verification cohort. In the established part, data were divided into group H and group N according to whether SpO2 >97 %. For group H (SpO2 ≤97 %), the regression equation was established between SFR and PFR. For group N (SpO2 >97 %), the correlation between each observation data and PFR was analyzed. Then, a new diagnostic process was established, and the reliability was verified with the Berlin definition set as the gold standard for diagnosis and classification. Results: There were 341 patients were included. Among them, 161 patients were used to establish the model, and 180 patients were used to verify the validity of the model. In this new diagnosis progress, when SpO2 ≤97 %, if SFR ≤352, ARDS may exist; when SpO2 >97 %, if FiO2min >39 %, there may be ARDS. The sensitivity, specificity, negative predictive value, positive predictive value, and accuracy of the new diagnosis progress for ARDS were 91.1 %, 76.7 %, 89.6 %, 79.6 %, and 83.9 %, respectively. Conclusion: The SpO2/FiO2 ratio demonstrates notable sensitivity and specificity in diagnosing ARDS, presenting as a credible alternative to PFR.Trail Registration Chinese Clinical Trial Registry Identifier: ChiCTR2000029217